Mastering cloud computing foundations and applications programming - Buyya, Rajkumar 1970-; Vecchiola, Christian; Selvi, S. Thamarai (Elsevier, Morgan Kaufmann, 2013)
"Key Features: Explains how to make design choices and tradeoffs to consider when building applications to run in a virtual cloud environment; Test and experiment with a live cloud system on the Aneka platform; Real-world case studies include scientific, business, and energy-efficiency considerations; Download examples and instructor support materials on the book's companion page.Cloud computing is a technological advancement that focuses on the way in which we design computing systems, develop applications, and leverage existing services for building software. It is based on the concept of dynamic provisioning, which is applied not only to services, but also to compute capability, storage, networking, and IT (Information Technology) infrastructure in general. Resources are made available through the Internet and offered on a pay-per-use basis from Cloud computing vendors. Today, anyone with a credit card can subscribe to Cloud services and deploy and configure servers for an application in hours, growing and shrinking the infrastructure serving its application according to the demand, and paying only for the time these resources have been used"..
Includes bibliographical references (pages 429-437) and index
Keywords: Cloud computing; Google App Engine; Cloud Computing